Do bacterial and fungal communities in soils of the Bolivian Altiplano change under shorter fallow periods? - Gomez-Montano, L.; Jumpponen, Ari M.; Gonzales, M. A.; Cusicanqui, J.; Valdivia, C.; Motavalli, P.; Herman, Michael A.; Garrett, Karen A. (My University, 2013)
This record provides supplemental material for this article: Gomez-Montano, L., A. Jumpponen, M. A. Gonzales, J. Cusicanqui, C. Valdivia, P. Motavalli, M. Herman, and K. A. Garrett. 2013. Do bacterial and fungal communities in soils of the Bolivian Altiplano change under shorter fallow periods? Soil Biology & Biochemistry 65:50-59. An R script for performing analyses in this paper is available at http://hdl.handle.net/2097/16206
Citation: Gomez-Montano, L., Jumpponen, A., Gonzales, M., . . . Garrett, K. (2013). Do bacterial and fungal communities in soils of the Bolivian Altiplano change under shorter fallow periods?. Soil Biology and Biochemistry, 65, 50-59. https://doi.org/10.1016/j.soilbio.2013.04.005
Keywords: 454 pyrosequencing; Andes; Bolivian highlands; Long fallow agriculture; Soil microbial communities